2s+3=13

Simple and best practice solution for 2s+3=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2s+3=13 equation:



2s+3=13
We move all terms to the left:
2s+3-(13)=0
We add all the numbers together, and all the variables
2s-10=0
We move all terms containing s to the left, all other terms to the right
2s=10
s=10/2
s=5

See similar equations:

| 8n-24=30n+20 | | a+5.92=12.29. | | 4g+2g-2g=20 | | 5y-y+7=9 | | 12+3x=2+x | | 3x-7=x+9x | | 511=-244-g | | 5(y+9)=20y | | 1.7+.3x=2.63 | | 8m-4m+6=-14 | | -1.9z-2.5=-1.5 | | -15m+21+5m=-19 | | 15c+c+4c-10c=20 | | 3(×-3)-5x=-3x-6 | | 7u+6=55 | | 22b=352 | | 18=s-144 | | 38x−2=18x+4 | | 3.5=-1.10x+300 | | -3=p-28 | | 11=|11+4x| | | 16c=352 | | 40.50=20.42+2x | | 4-2(v+6)=2 | | -6.78=-2.3+3.2y | | 3x+7=-11+x | | 8m-4m+6=-14 | | -3.5=-70x+300 | | 3/4x+(-4.5)=4.5 | | 96=239-t | | 7/d=-3 | | 1.5(2b+6)=-3(4b-1) |

Equations solver categories